Staying Connected: Reaching Out to Psychiatric Patients During the Covid-19 Lockdown Using an Online Blog - Astrid Lehner; Klaus Nuißl; Winfried Schlee; Berthold Langguth (Frontiers Media S.A., 2020)
Health systems worldwide are challenged by the coronavirus pandemic and all medical specialties have struggle to meet the conflicting requirements for virus containment on the one hand and treatment of other medical conditions on the other. This holds true also for psychiatry. Per se, psychiatric patients are highly vulnerable to suffer from social isolation and loneliness. As a result of the Covid-19 pandemic and lockdown measures, unfortunately, this vulnerability is even further increased. As a part of its pandemic risk management, the outpatient clinic of the Psychiatric District Hospital Regensburg launched an online blog as a means of assisting patients who were required to stay home. Aim of the blog was to stay by patients' side in those uncertain times by offering an online connection to their therapists, by providing important information about the pandemic situation, by offering some ideas on how to build a daily routine and how to meaningfully spend their time at home during the lockdown. We also aimed at involving patients as experts in their own affairs by inviting them to contribute to the blog's shape and content. As a result of coordinated team effort, it was possible to launch a blog within few days, and this was perceived helpful by many patients. Overall, however, patient involvement turned out to be a challenge requiring more attention in future work.